Strukturerhaltende Approximation linearer verteilt-parametrischer PCHD-Systeme - Harkort, Christian; Deutscher, Joachim (at - Automatisierungstechnik, 2012)
In this contribution an approximation approach for linear distributed-parameter port controlled Hamiltonian systems with damping (PCHD systems) is presented that allows for the preservation of the PCHD structure of the original system. Futhermore, it is possible to assure that the stability margin of the approximation satisfies a lower bound that depends on the dissipativity of the infinitedimensional system operator. The presented approximation method is based on a generalized version of the Petrov-Galerkin approximation and has free parameters that can be used to achieve approximations with matching moments. The results of the paper are demonstrated by approximating a heat conducting system. © Oldenbourg Wissenschaftsverla
Keywords: Krylov subspace method; Linear infinite-dimensional systems; PCHD systems; Structure preserving approximation